1999
DOI: 10.1080/00223989909599727
|View full text |Cite
|
Sign up to set email alerts
|

Extraversion and Exercise Addiction

Abstract: Extraversion has been suggested as a factor associated with addiction. This claim was tested in relation to exercise addiction. Twelve exercise addicts were compared with 12 nonaddicted individuals who were committed to regular exercise and with 12 nonexercising individuals drawn from the same student population. Addicted exercisers did not differ from nonaddicted exercisers in extraversion, although exercisers as a group were more extraverted than nonexercisers. The results are interpreted as evidence against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Despite one demographic variable (i.e., exercise engagement) explaining the highest percent of the variance (i.e., 21.5%), extraversion proved to be the second best predictor accounting for 14% of the variance. Based upon these observations, extraversion as a predictor of exercise addiction remains consistent with previous findings (e.g., Costa and Oliva 2012;Courneya and Hellsten 1998;Mathers and Walker 1999;Yeung and Hemsley 1997).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Despite one demographic variable (i.e., exercise engagement) explaining the highest percent of the variance (i.e., 21.5%), extraversion proved to be the second best predictor accounting for 14% of the variance. Based upon these observations, extraversion as a predictor of exercise addiction remains consistent with previous findings (e.g., Costa and Oliva 2012;Courneya and Hellsten 1998;Mathers and Walker 1999;Yeung and Hemsley 1997).…”
Section: Discussionsupporting
confidence: 79%
“…A few studies have indicated that high extraversion and low agreeableness have an association with exercise (Costa and Oliva 2012;Hausenblas and Giacobbi 2004;Mathers and Walker 1999). Mathers and Walker (1999) reported that nonexercisers were significantly less extraverted compared to the exercisers. However, there was no significant difference in extraversion scores between addicted and non-addicted exercisers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bianchi and Phillips (2005) found that problematic mobile phone use was positively related to Extroversion, a finding supported by Augner and Hacker (2012) who also found it to be positively associated with Neuroticism. Exercise addiction has been claimed to be related to Extroversion albeit one study failed to substantiate that claim (Mathers & Walker, 1999). Kern (2010) found that exercise addiction was positively related to Neuroticism and Openness among students, whereas it was positively related to Agreeableness and Openness among recreational practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Sensation seeking has also been linked to aberrant driving behavior. 51 Although the connection to addiction is not definitive, 52,53 it has generally been established that extraverts are more susceptible to addictive behaviors such as alcoholism 54 and drug addiction. 55 Secondly, suboptimal arousal may mean that extraverts are more susceptible to problem use of mobile phones on the grounds that they are more likely to seek out social situations.…”
Section: Extraversion and Problem Use Of Mobile Phonesmentioning
confidence: 99%